A new survey of the U.S. bilateral repo market: A snapshot of broker-dealer activity - Viktoria Baklanova; Cecilia Caglio; Marco Cipriani; Adam Copeland (Federal Reserve Bank of New York, 2016)
We provide aggregate statistics on U.S. dealers' bilateral repurchase agreements and economically equivalent securities lending activities. The data were collected from the U.S.-affiliated securities dealers of nine bank holding companies under a voluntary pilot program run by the Office of Financial Research and the Federal Reserve System with input from the Securities and Exchange Commission. We find that the majority of this activity involves the delivery or receipt of U.S. Treasuries, with equities a distant second. The most common maturity is one day. Finally, rates are widely dispersed across asset classes.
Keywords: E44; G24; G12; 330; bilateral repo; short-term funding; financial market